A new species in the Simulium vernum group from the Northern Limestone Alps of Austria: Simulium hasekei (Diptera: Simuliidae) - Seitz, Gunther; Adler, Peter H.; Remschak, Christina (Zootaxa, 2021)
Simulium hasekei new species is described from the Alps of Austria. It is characterized by a broad trapezoidal ventral plate in the male, long straight arms of the genital fork in the female, a well-developed anterodorsal projection on the weakly woven cocoon, and a deep rounded postgenal cleft and strong paralateral hypostomal teeth in the larva. The species is chromosomally most similar to the Holarctic S. bicorne Dorogostaisky, Rubtsov & Vlasenko and S. fontinale Radzivilovskaya and the Nearctic S. craigi Adler & Currie. It is known from one small ponor brook, in association with S. aureum (Fries) s. s., S. beltukovae (Rubtsov), and Simulium vernum Macquart s. s.